Antibacterial Derivatives of Ciprofloxacin to Inhibit Growth of Necrotizing Fasciitis Associated Penicillin Resistant Escherichia coli. (2nd May 2013) - Bartzatt, Ronald; Cirillo, Suat L. G.; Cirillo, Jeffrey D.
Abstract : Escherichia coli ( E. coli ) is associated with necrotizing fasciitis (type I) and can induce enough damage to tissue causing hypoxia. Three ester derivatives of the broad-spectrum antibiotic ciprofloxacin were placed into bacteria culture simultaneously with the parent ciprofloxacin (drug 1) to ascertain the level of antibacterial activity. The n-propyl (drug 2), n-pentyl (drug 3), and n-octyl (drug 4) esters of ciprofloxacin were synthesized under mixed phase conditions and by microwave excitation. The formation of ester derivatives of ciprofloxacin modified important molecular properties such as Log P and polar surface area which improves tissue penetration, yet preserved strong antibacterial activity. The Log P values for drugs 1, 2, 3, and 4 became −0.701, 0.437, 1.50, and 3.02, respectively. The polar surface areas for drugs 1, 2, 3, and 4 were determined to be 74.6 Angstroms 2, 63.6 Angstroms 2, 63.6 Angstroms 2, and 63.6 Angstroms 2, respectively. These values of Log P and polar surface area improved tissue penetration, as indicated by the determination of dermal permeability coefficient (K p ) and subsequently into the superficial fascial layer. All drugs induced greater than 60% bacterial cell death at concentrations less than 1.0 micrograms/milliliter. The ester derivatives of ciprofloxacin showed strong antibacterial activity toward penicillin resistant E. coli .